Generals and scholars : military rule in medieval Korea - Shultz, Edward J. (University of Hawai'i Press, 2000)
Generals and Scholars is the first work in English to examine fully military rule during the Koryo. Although it lasted for only a century, the period was one of dynamic change -- a time of institutional development, social transformation, and the reassertion of the civil service examination and Confucian ideology coupled with the flowering of Son (Zen) Buddhism.